Language transparency in Functional Discourse Grammar: The case of Quechua (Linguistics in Amsterdam, 2011)
Despite presenting remarkbale transparent features in its grammar, which translates, for instance, into the absence of opaque morphosyntactic operations, such as tense copying, grammatical gender and agreement, Quechua can not be regarded as a representative case of language transparency. As a matter of fact, it presents features which, within the context of Functional Discourse Grammar, can be regarded as non-trasparent such as, for example, the presence of apposition and cross-reference and the existence of morphosyntactic operations, such as raising and morphosyntactic alignment. Interestinlgy, evidence is found in this study with respect to the crucial role of the phenomenon of grammaticalization in the development of language opaquenes.